(untitled) (Revista Iberoamericana de Bioética, 2020)
Our goal in this article was to examine the environmental impacts of mining in the district of Moatize, Mozambique from the perspective of the Sustainable Development Goals within the agenda of environmental bioethics. Therefore, an exploratory, cross-sectional and qualitative research methodology was developed based on relevant scientific literature, news and legislation, observation in situ and interviews with local residents. The environmental impacts of mining in Moatize are well known, however there has been no effective State intervention, both with regard to its civil liability for the environmental damage from coal dust emissions, as well as the prevention and mitigation of impacts to the health and social organisation of the population. Approaching this theme from the perspective of environmental bioethics involves a dialogue between different actors for solutions to mitigate vulnerabilities. We therefore suggest that multidisciplinary committees for standards, discussion and education be established, with the participation of the community in decisions of common interest.